2022
DOI: 10.1007/s12035-022-03025-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific Mutations in the Cholesterol-Binding Site of APP Alter Its Processing and Favor the Production of Shorter, Less Toxic Aβ Peptides

Abstract: Excess brain cholesterol is strongly implicated in the pathogenesis of Alzheimer’s disease (AD). Here we evaluated how the presence of a cholesterol-binding site (CBS) in the transmembrane and juxtamembrane regions of the amyloid precursor protein (APP) regulates its processing. We generated nine point mutations in the APP gene, changing the charge and/or hydrophobicity of the amino-acids which were previously shown as part of the CBS. Most mutations triggered a reduction of amyloid-β peptides Aβ40 and Aβ42 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Cholesterol and APOE regulate APP cleavage (Howland et al, 1998;Mills and Reiner, 1999). Mutations in the APP cholesterol-binding site alter APP processing to form less toxic Aβ peptides (Hanbouch et al, 2022). Free cholesterol fosters Aβ self-assembly on membranes (Hashemi et al, 2022), likely along with degraded myelin basic protein as noted below (Zhan et al, 2018).…”
Section: Cholesterol Binding To Abeta and App Fostering Formation Of ...mentioning
confidence: 99%
“…Cholesterol and APOE regulate APP cleavage (Howland et al, 1998;Mills and Reiner, 1999). Mutations in the APP cholesterol-binding site alter APP processing to form less toxic Aβ peptides (Hanbouch et al, 2022). Free cholesterol fosters Aβ self-assembly on membranes (Hashemi et al, 2022), likely along with degraded myelin basic protein as noted below (Zhan et al, 2018).…”
Section: Cholesterol Binding To Abeta and App Fostering Formation Of ...mentioning
confidence: 99%
“…As the interaction of different APP fragments with cholesterol also seems to be an important factor in its processing [ 7 , 27 , 28 , 30 , 38 , 39 , 40 ], we decided to investigate if it would be possible to detect any difference in APP clusterization and APP-induced changes in a membrane structure for different concentrations of cholesterol in the lipid bilayer. The set of corresponding topographies is displayed in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…As for the APP, its fragment APP 672–770 , often referred to as C99, was also studied to be a cholesterol-binding site [ 27 ], especially the loop region connecting its juxtamembrane helix and N-terminal part of transmembrane helix [ 26 , 28 , 29 ]. It was later shown that indeed different mutations in the transmembrane domain of APP significantly affect cholesterol binding [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain genes and molecular pathways linked to the mechanisms of neurodegenerative diseases modify their expression with progressing skin aging, possibly due to the shared ectodermal origin of the skin and nervous system [ 313 ]. BACE1 (β-secretase 1), an enzyme that degrades amyloid-β 1-40 and amyloid-β 1-42 , generates a shorter amyloid-β 1-34 peptide [ 314 ], which has been identified in human skin and could serve as a possible marker of amyloid-β degradation [ 315 ]. Additionally, a study showed that the majority of the 125 I-labeled amyloid-β 1-40 was detected in the skin with only a minor amount in the brain, demonstrating that amyloid-β produced in the brain can be cleared in the periphery [ 232 ].…”
Section: Amyloid-β Clearance In the Peripherymentioning
confidence: 99%